Effect of currency exchange rate fluctuations on Aid Effectiveness in the Health Sector in Zambia - Chansa, Collins; Sundewall, Jesper; Östlund, Numi (Health policy and planning, 2018)
Abstract. Development assistance for health (DAH) remains a significant and important source of health financing in many low and lower middle-income countries.
Advance access publication date: 22 June 2018
Gesehen am 10.04.2019